(untitled) (The Journal of Plant Protection Sciences, 2024)
Morphology of female perineal pattern (area around anus and vulva) of the root knot nema tode (Meloidogyne spp.) is studied to identify the species under the genus as this was origi nally proposed by Chitwood (2). Several at tempts (7,8,6,4,3) have been made to improve the technique for preparation and photograph ing of perineal patterns of Meloidogyne spp. Most of the cases cuticular patterns are photo graphed to record the morphological charac ters therein and stored for a short period and later disposed off. However, preservation of the patterns for subsequent study is much not known to those working with routine identifica tion of Meloidogyne spp. In fact, the patterns on the Meloidogyne spp. female perineum disappear with the time due to dehydration and decaying of adhering body tissues.